2008
DOI: 10.1016/j.ejcts.2008.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and pathophysiology of atrioventricular block following mitral valve replacement and ring annuloplasty

Abstract: Data collected in this study showed that, sotalol and amiodarone as well as a prolonged cross-clamp time may slightly influence the 23% incidence of postoperative AVB. The morphological investigation showed that the AV node artery runs in close proximity to the annulus in 23% of cases. We speculate that damage of the AV node artery may play a role in development of AVB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 12 publications
6
43
1
5
Order By: Relevance
“…In our study, incidence of AVB with TCP in 17% (187 cases) of the total of 1102 patients undergoing heart valve surgery during the period. However, most AVBs proved to be transient and reversible: only 1.27% of these patients developed DPM need to implant this hospital stay, incidence similar to the literature (1.3% to 9.7%) this association POCS [1][2][3][7][8][9].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In our study, incidence of AVB with TCP in 17% (187 cases) of the total of 1102 patients undergoing heart valve surgery during the period. However, most AVBs proved to be transient and reversible: only 1.27% of these patients developed DPM need to implant this hospital stay, incidence similar to the literature (1.3% to 9.7%) this association POCS [1][2][3][7][8][9].…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, if there is direct injury of the conduction system (prolonged ischemia, damage by removal of calcium from the valve structures, or deep stitches, etc.) Disorder is expected to drive greater likelihood of permanent and irreversible [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, nevertheless, are in line with prior single‐center reports showing pacemaker rates of 13% to 28% after TV surgery and higher odds of needing a pacemaker after TVR versus TVr 37, 38. Several anatomical and technical factors have been implicated in these high rates of pacemaker dependency after TV surgery, including intraoperative hypothermia, cardiopulmonary bypass duration, and the proximity of the atrioventricular node and the atrioventricular nodal artery to the tricuspid annulus 39, 40. (2) New dialysis requirements were high after isolated TVR and TVr (5.5% and 4.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The first study included 115 patients and showed an incidence of CDs of 23% and PPI in 2.6% [12]. The second study included 391 patients undergoing mitral valve surgery (147 with MVR) and showed CDs in 23.5% and PPI in 4% [13]. Understanding the risk factors and natural history of CD and AA in patients undergoing MVR may influence both the timing of pacemaker implantation and the strategy to restore sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%